Telomerase inhibition by new di- and trisubstituted acridine derivatives - Negrutska, V.V.; Saraieva, I.V.; Kostina, V.G.; Alexeeva, I.V.; Lysenko, N.A.; Dubey, I.Ya. (Вiopolymers and Cell, 2016)
Aim. To study a series of new acridine derivatives containing two basic fragments able to bind to quadruplex DNA at C-4 and C-9 positions as potential telomerase inhibitors. Methods. TRAP assay was used to determine the activity of compounds in vitro. Results. A number of acridines inhibiting the enzyme at micromolar concentrations were found, with IC₅₀ = 2.6 µM for the most active compound. Conclusions. The introduction of a highly basic N,N-dimethylaminoalkyl group at the C-9 position of the acridine core results in a strong increase of biological activity of compounds, and a 5-methyl substituent further enhances it. Мета. Дослідити серію нових похідних акридину, що містять у положеннях С-4 і С-9 два основні фрагменти, здатні зв’я-зу-ва-ти-ся з квадруплексною ДНК, як потенційних інгібіторів теломерази. Методи. Для визначення активності сполук in vitro вико-ристано метод TRAP. Результати. Виявлено ряд акридинів, що інгібують фермент у низьких мікромолярних концентраціях, для найактивнішого з яких ІС₅₀ = 2.6 мкМ. Висновки. При введенні високоосновної N,N-диметиламіноалкільної групи в положення С-9 акридинового ядра біологічна активність сполук різко зростає, а 5-метильний замісник додатково збільшує її. Цель. Изучить серию новых производных акридина, содержащих в положениях С-4 и С-9 два основных фрагмента, способных связываться с квадруплексной ДНК, как потенциальных ингибиторов теломеразы. Методы. Для определения активности веществ in vitro использован метод TRAP. Результаты. Обнаружен ряд акридинов, ингибирующих фермент в низких микромоляных концентрациях, для самого активного из которых ІС₅₀ = 2.6 мкM. Выводы. При введении высокоосновной N,N-диметиламиноадкильной группы в положении С-9 акридинового ядра биологическая активность соединений резко возрастает, а 5-метильный заместитель дополнительно увеличивает ее.